Relation-Theoretic Common Fixed Point Theorems for a Pair of Implicit Contractive Maps in Metric Spaces - Eke, Kanayo Stella; Davvaz, Bijan; Oghonyon, Jimevwo Godwin (Communications in Mathematics and Applications, 2019)
In this manuscript, we demonstrate some common fixed point theorems for a pair of weakly compatibleness of the operators under implicit contractive properties in metric spaces endowed with binary relation. An illustration is establish to emphaize the cogency of our results. The outcome of our proofs are unification of several relation theorems existing in the literature.